Financial Plan for Students who Dare to Dream - Hardianto Ramadhan; Catur Budi Wicaksono; Irwan; Nini Andriani; Ayu Putri Utami (Universitas Muhammadiyah Palu, 2025)
This article discusses the importance of financial planning for university students in Indonesia who face financial challenges in pursuing their education and dreams. With low levels of financial literacy, college students need to understand personal financial management, including budgeting, saving, and finding additional sources of income. The research shows that financial education in higher education is critical to improving students' understanding of financial management and investment, which are key elements in achieving financial independence. In addition, the research also examines the financial planning challenges faced by students and workers, as well as the role of gender in investment. The findings show that university students have an initial awareness of financial planning, but are often hampered by limited resources. Meanwhile, workers, while more knowledgeable about investments, also struggle to set aside funds due to the high cost of living. Students' self-control is better than workers, who experience more pressure. Gender-based investment findings show that men tend to be more risk-taking, while women are more conservative. Motivation and financial literacy are key factors in effective financial planning. This article emphasizes the importance of better financial education to improve financial literacy among college students, so that they can manage their finances wisely and achieve their financial goals.